REEs fractionation and sedimentary implication in surface sediments from eastern South China Sea - 张霄宇 张富元 陈欣 章伟艳 邓涵 (Journal of rare earths, 2012)
To get features of rare earth elements （REEs） fractionation, 106 surface sediment samples from eastern South China Sea were determined for REEs combined with major and trace elements by ICP-MS. The distribution pattern of REEs, strong correlation between REEs and Al, North American shale composite （NASC） normalization all suggest a dominant crustal source for REEs in the research area. However distinct fractionation among REEs was observed in surface sediment from area with water depth over 2000 m, confirmed by the strong positive correlation among light rare earth elements （LREEs） and among heavy rare earth elements （HREEs） but weaker relationship between LREEs and HREEs. Eluviation by Cl- might be a key role on the fiactionation of REEs, comparing with factors such as grain size, co-precipitation with Fe and Mn hydroxide, calcareous and siliceous biogenic precipitation. The fractionation among REEs could be used as index to illustrate the sedimentary environment in reverse.